2011
DOI: 10.1016/j.ijsu.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and surgical outcome for pulmonary aspergilloma: Nine year retrospective observational study in a tertiary care hospital

Abstract: Pulmonary aspergilloma is common in developing countries like India in which there is high prevalence of pulmonary tuberculosis. Surgical resection of pulmonary aspergilloma is effective in preventing recurrence of symptoms including hemoptysis. We recommend early surgical resection of symptomatic aspergilloma with reasonable complications. Pre-operative preparation of the patients, meticulous surgical technique and post-operative chest physiotherapy reduces the rate of complications. Complications may still o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 19 publications
0
17
1
1
Order By: Relevance
“…Air leaks occurred in 1% to 23% of patients in previous studies [25]. However, in our series only 1 patient in the lobectomy group had persistent air leak (>14 days).…”
Section: Commentcontrasting
confidence: 66%
“…Air leaks occurred in 1% to 23% of patients in previous studies [25]. However, in our series only 1 patient in the lobectomy group had persistent air leak (>14 days).…”
Section: Commentcontrasting
confidence: 66%
“…9 In addition, surgical resection of aspergillomas has a 2% to 3% mortality rate, and the morbidity is approximately 30%. 8,[10][11][12][13][14] Although some have suggested that the morbidity and mortality of such surgery has improved, 15 the fact remains that most patients with aspergilloma are inadequate surgical candidates. Although bronchial artery embolization (BAE) is usually transiently effective to control hemoptysis from an aspergilloma, revascularization commonly occurs, which often leads to future recurrent bleeding [16][17][18][19] that is less responsive to subsequent BAE.…”
Section: Resultsmentioning
confidence: 99%
“…When medical therapy is ineffective, surgical debulking of aspergillomas is the treatment of choice, with a reasonable safety profile and good long‐term outcomes . Unfortunately, owing to the clinical characteristics of the affected population, a high percentage of patients are very poor surgical candidates, which leads to limited options and high mortality.…”
Section: Discussionmentioning
confidence: 99%